Archipelagic Insights in Solving National Cultural Conflicts in Indonesia - Mukri, Waal Mukhayun; Waspiah, Waspiah (Indonesian Journal of Pancasila and Global Constitutionalism, 2023)
The Archipelagic Insight is one of the important things, not only in strengthening the national character but also in positioning various problems in the eyes of nationalism and Indonesianness. This study aims to analyze the role of archipelago insight in solving various national cultural conflicts. The method used in this study is a literature study, in which the author examines various theories and research results related to the archipelago's insight as a means of solving problems of national cultural conflict. This study finds and emphasizes that with the diversity of ethnicity, race, religion, belief and culture in Indonesia, various potential conflicts always arise. The heterogeneous character of the Indonesian nation becomes a conflict related to culture which is very likely to occur. In addition, in this study, the archipelago insight is considered capable of resolving various potential conflicts, including cultural conflicts, whether through the Pancasila philosophy approach, regional, socio-cultural, or historical aspects.